A phylogeny of Astyanax (Characiformes: Characidae) in Central and North America - Schmitter-Soto, Juan J. (Zootaxa, 2016)
A phylogeny is presented for 34 species of Astyanax, 27 of them once included within A. aeneus or A. fasciatus in Central America and Mexico, based on 52 morphological characters (mostly osteological, but also pigmentation and meristics), with three outgroups. Monophyly is not supported for A. aeneus s. lat., as Brazilian species such as A. fasciatus s. str. and others occur also within that clade. There were only five resolved clades, three of them including both Brazilian and Central American species, one purely Nicaraguan, and one for central-northern Mexico and Texas. Coincidence with previous cladistic hypotheses is only partial. The genus Bramocharax Gill is not recovered, and thus confirmed as a synonym of Astyanax Baird & Girard. The findings point at a more complex biogeographic history of the region than usually recognized.